Perfil epidemiológico e funcional dos acidentados de trânsito atendidos em um serviço de fisioterapia em Fortaleza - Vasconcelos, Samara Sousa (2010)
The present study it had as objective main to analyze the profile epidemiologist and to carry through a functional evaluation of the taken care of victims of traffic in a service of physiotherapy in Fortaleza. For such, a quantitative and transversal study, developed of May the November of 2009 was carried through, in the ABCR-center. They had participated of this, patient rough of traffic carrying through treatment in the institution, greater of 18 years and concordant in participating of the research. For collection of the data, a script was used, instrument FIM and Scale de Social Participial. The data had been analyzed with software SPSS 15.0. 57 patients, 53 men and 4 women had been evaluated, with medium age of 37±14 years, being the majority (49.1%) married and with complete basic education (42.1%). When considering the working situation before and after the accident, met significant difference between same (p<0.01), where after the accident the majority (80.7%) it wasn’t working. The motorcycle was the vehicle most involved in the accidents (70.2%) e the type most recurrent was collision (54.4%). When comparing the acts average in accordance with the type of involved vehicle, met difference significant (p=0.04) it enters the accidents with motion and with vehicle not motorized or without no vehicle. The breakings had been predominant (73.7%) and the inferior members were the most injuried body region (60%). When comparing the injured body region in accordance with the involved vehicle, met that the motorcycle affect predominantly the members and the too much vehicles the region of the head (p=0.02). The majority of the patients presented complete independence for the total FIM (54.4%), motor (42.1%) e cognitive (86%).The locomotion was the subdomain that presented the biggest degrees of dependence. How much to the social participation, the majority (28.1%) it presented serious restriction of the same one. When correlating the MIF with the Social Participation through the test of correlation of Spearman, got a moderate negative correlation, statistical significant (R=-0.54, p<0.01). In the multivariate analysis of the Social Participation through multiple regression, they had entered in the clarifying model of the same a FIM motor, the time of internment and the civil state (p=0.01; p=0.01; p=0.09, respectively). Concluded that the majority of the participants were men, young adults and singles; that motorcycle was the vehicle more involved and the collision was the type more recurrent; that the factures were the most prevalent injuries and the lower limbs were the most affected; considering the vehicle involved, there was difference as the victims’ age, as well as, the lesional profile (affected region); the people were more prevalent, who presenting functional independence, but in considering the questions of it, the most affected was the locomotion; that stood out individuals with severe restriction of social participation; that motor FIM, hospitalization time and marital status were explanatory of social participation.